PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN, DAN INFLASI TERHADAP BELANJA MODAL DENGAN PERTUMBUHAN EKONOMI SEBAGAI VARIABEL INTERVENING PERIODE TAHUN 2015 – 2018 (Penelitian di Kota/Kabupaten Provinsi Banten) - Salim, Agus (Pascasarjana Universitas Sultan Ageng Tirtayas, 2019)
This study aims to examine the effect of local revenue, balance funds, and inflation on capital expenditure with economic growth as an intervening variable in the City / Regency of Banten Province. The sample from this study was 8 regencies / cities of Banten Province. which consists of Kab. Lebak, Kab. Pandeglang, Kab. Serang, Kab. Tangerang, Cilegon City, Tangerang City, Serang City, South Tangerang City. With the sampling technique using the saturated sample method. This data is obtained from the website of the Director General of Financial Balance of Regional Governments through www.djpk.depkeu.go.id and BPS of the Banten Provincial Government. The data in this study were processed using SPSS software. The results of this study conclude that the regional original income variable has a positive effect on economic growth, balancing funds have a positive effect on economic growth, inflation has a negative effect on economic growth, regional original income has a positive effect on Capital Expenditure, positive influential balancing funds adapts the realization of capital expenditure, Inflation has a negative effect on capital expenditure realization, economic growth has a positive effect on capital expenditure realization, regional original income has a positive effect on capital expenditure realization mediated by economic growth, balancing funds have a positive effect on capital expenditure realization mediated by economic growth, and inflation has a positive effect on realization of capital expenditure is mediated by economic growth.